Neuronal activation modulates enhancer activity of genes for excitatory synaptogenesis through de novo DNA methylation - Tomonori KAMEDA; Hideyuki NAKASHIMA; Takumi TAKIZAWA; Fumihito MIURA; Takashi ITO; Kinichi NAKASHIMA; Takuya IMAMURA (The Society for Reproduction and Development, 2021)
Post-mitotic neurons do exhibit DNA methylation changes, contrary to the longstanding belief that the epigenetic pattern in terminally differentiated cells is essentially unchanged. While the mechanism and physiological significance of DNA demethylation in neurons have been extensively elucidated, the occurrence of de novo DNA methylation and its impacts have been much less investigated. In the present study, we showed that neuronal activation induces de novo DNA methylation at enhancer regions, which can repress target genes in primary cultured hippocampal neurons. The functional significance of this de novo DNA methylation was underpinned by the demonstration that inhibition of DNA methyltransferase (DNMT) activity decreased neuronal activity-induced excitatory synaptogenesis. Overexpression of WW and C2 domain-containing 1 (Wwc1), a representative target gene of de novo DNA methylation, could phenocopy this DNMT inhibition-induced decrease in synaptogenesis. We found that both DNMT1 and DNMT3a were required for neuronal activity-induced de novo DNA methylation of the Wwc1 enhancer. Taken together, we concluded that neuronal activity-induced de novo DNA methylation that affects gene expression has an impact on neuronal physiology that is comparable to that of DNA demethylation. Since the different requirements of DNMTs for germ cell and embryonic development are known, our findings also have considerable implications for future studies on epigenomics in the field of reproductive biology.